PELUANG INKLUSI KEUANGAN PERBANKAN SYARIAH DI KOTA BIMA PROVINSI NUSA TENGGARA BARAT - Dwi Aulia; Unggul Priyadi (Jurnal Ekonomi Syariah Darussalam, 2023)
The presence of Islamic banks in the midst of conventional banking is to offer the banking system as an alternative for Muslims who need or wish to obtain banking services without having to violate the prohibition of usury. From the beginning of its emergence, the development of Islamic banking has become increasingly recognized and has played a major role in the economy of the Indonesian people, especially the Muslim community. Even so, there is still a public perception that considers Islamic banking to be the same as conventional banking and considers convenience in conventional access to be easier. This study aims to analyze the Opportunities for Financial Inclusion of Islamic Banking in the City of Bima, West Nusa Tenggara Province. The subject of this research is the people in Bima City. This research uses quantitative method. The data collection method uses a non-probability sampling technique using a questionnaire. This research uses logistic regression analysis method. The results showed that there was a simultaneous influence between the Islamic banking financial inclusion variables and partially showed significant results from the age variable of 0.02 the sig job variable. 0.01 and the education variable is 0.05 while gender does not significantly influence the opportunities for Islamic banking financial inclusion in Bima City with a sig value of 0.347.